Premenstrual Syndrome and Premenstrual Dysphoric Disorder From the theory to the clinical approach - Maciejewska, Danuta; Kapłon, Kamil; Wojtala, Laura; Pawlak, Weronika; Pawłocik, Weronika; Dudkiewicz, Michalina (Journal of Education, Health and Sport, 2023)
Mental state of women during their reproductive age fluctuates with the changes in menstrual cycle phases. However, only some of them develop psychiatric disorders. The aim of the study is to present the importance of Premenstrual Syndrome and Premenstrual Dysphoric Disorder as important diseases at the edge of gynecology and psychiatry. Many symptoms classified as premenstrual have been described in the literature. Mood swings turn out to be the most important psychological symptom of the disorders whereas bloating is a common somatic manifestation. Despite some difficulties in the establishment of the exact cause, diagnostic criteria for both have been developed and are the basis on which the clinician makes a final diagnosis. The paper also describes the current state of knowledge about the treatment of Premenstrual Syndrome and Premenstrual Dysphoric Disorder. The continuous increase in the importance of non-pharmacological methods such as lifestyle changes and cognitive-behavioral therapy was emphasized. Manners of pharmacological treatment were also described, including SSRIs and hormonal drugs, which should be selected individually, depending on the characteristics of the clinical picture.